2018
DOI: 10.1530/eje-17-0403
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the gut microbiome: a systematic review of the effect of bariatric surgery

Abstract: There is strong evidence to support a considerable alteration of the gut microbiome after bariatric surgery. Deeper investigations are required to confirm the mechanisms that link the gut microbiome and metabolic alterations in human metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
98
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(108 citation statements)
references
References 59 publications
8
98
0
2
Order By: Relevance
“…These bacteria have been related to chronic low-grade inflammation and metabolic diseases (e.g. obesity and type 2 diabetes) in humans and rats (Pataky, et al, 2016;Guo, et al, 2018;Tang, et al, 2018;Kong, et al, 2019). In rabbits, low-grade inflammation and fat deposition have been known to negatively impact growth (Sigrist-Flores, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These bacteria have been related to chronic low-grade inflammation and metabolic diseases (e.g. obesity and type 2 diabetes) in humans and rats (Pataky, et al, 2016;Guo, et al, 2018;Tang, et al, 2018;Kong, et al, 2019). In rabbits, low-grade inflammation and fat deposition have been known to negatively impact growth (Sigrist-Flores, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Observed persistent increase in Enterobacteriaceae after surgery, confirms previous sustained changes reported in humans and animal models (rats), associated with increased pH 7, 24, 28, 29 . Other main differences, exposure to undigested nutrients and biliopancreatic enzymes, may play important roles in the microbial composition, intestinal permeability and intestinal adaptation 30 . Since increased intestinal permeability is associated with inflammation and reductions in alpha diversity, which is also associated with obesity, it is questionable whether restoration of alpha diversity to baseline level may also reflect persistent inflammation in the post-surgery state at 6 months, which has been previous related to increase in Enterobacteriaceae 16 .…”
Section: Discussionmentioning
confidence: 99%
“…A diverse array of strategies to manipulate the gut microbiome exist and include dietary interventions, probiotics (culture of living microorganisms), prebiotics (fermentable dietary fibers that stimulate the growth and survival of probiotics), synbiotics (combination of probiotics and prebiotics), antibiotics, and FMT . Moreover, bariatric surgery results in rapid and sustained shifts in the gut microbiome . Damms‐Machado et al found that the gut microbiome in adults with obesity who underwent bariatric surgery shifted within 6 months after surgery toward a microbial profile found in adults with normal body weight.…”
Section: Gut Microbiome‐targeted Therapy In the Management Of Nafldmentioning
confidence: 99%
“…(1) Moreover, bariatric surgery results in rapid and sustained shifts in the gut microbiome. (133) Damms-Machado et al (134) found that the gut microbiome in adults with obesity who underwent bariatric surgery shifted within 6 months after surgery toward a microbial profile found in adults with normal body weight. Recent studies have revealed the existence of distinct and niche-specific microbial communities along the length of the gastrointestinal tract and that the composition of these communities influence successful engraftment of exogenous microbes, (135,136) suggesting that future microbial interventions may be personalized based on an individual's gut microbiome.…”
Section: Gut Microbiome-targeted Therapy In the Management Of Nafldmentioning
confidence: 99%